Role of the neodymium YAG laser in the management of tracheal tumours. - George, P J (1987)
Twenty one patients with tracheal tumours (10 primary and 11 secondary) have been treated with the neodymium YAG laser under general anaesthesia. Fourteen of these patients presented with impending asphyxia and in 11 cases this was dramatically relieved with emergency laser treatment. The improvements in peak expiratory flow (PEF) ranged from 26% to 512%. The three patients who did not respond were immediately given other treatments but died in hospital. The remaining seven patients were not in severe respiratory distress and were treated electively; all were thought to have benefited from their treatment, the mean increase in PEF being 36%. The improvement obtained in the 11 patients who responded to emergency laser treatment provided time in which to assess the disease carefully and plan the most appropriate longer term management with surgery, radiotherapy, tracheal stenting, or repeat laser treatment. The patients who were treated electively have either not required further treatment of have been managed with repeat laser treatments alone. Laser treatment provides an excellent method of resuscitating patients with life threatening tracheal obstruction and enables subsequent management to be carefully planned. In some cases this longer term management should be with further laser treatment alone.